Determinan Kemandirian Lansia dalam melakukkan Instrumental Activity Daily Living (IADL) di Wilayah Kerja Puskesmas Balauring Kec. Omesuri Kab.Lembata-NTT - Rosina Kardina Kidi Hurek (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
Research aims to determine the determinants of the independence of the elderly in conducting IADL in the work area of ​​the Balauring Health Center in district Omesuri, Lembata-NTT 2018. Elderly dependence occurs when they experience decreased body functions and cannot adapt to these conditions. One of the instruments to assess the health status of the elderly is IADL. The research method is quantitative research equipped with qualitative data with Cross Sectional design. The total sample is 157 people. Data analysis techniques include univariate, chi square, and simple logistic regression analysis. Qualitative data analysis techniques using in-depth interviews. The results showed that there was a significant relationship between age, health status, role of midwife, and physical activity with independence in doing IADL where p value < 0,05. Multivariate analysis of logistic regression obtained role of midwife variables with an Exp (B) value of 2,190 which means that the role passive midwife has of risk making independence of edelry doing IADL 2,190 times bigger than the role of active midwives. The results of qualitative research found that the cause of many elderly people who are independent in conducting IADL is that most of the elderly are still actively working and productive in generating income so that the elderly self-confidence is higher and has sufficient physical activity as seen from the type of work that is occupied, that is, most work as farmers and traders. In addition, this role of midwives who are active in the village greatly impacts the independence of the elderly in conducting IADL. Keyword : Elderly, independence of the elderly, Instrumental Activity Daily Living (IADL)